Flights - Tokarczuk, Olga, 1962- (Riverhead Books, 2018)
From the incomparably original Polish writer Olga Tokarczuk, Flights interweaves reflections on travel with an in-depth exploration of the human body, broaching life, death, motion, and migration. Chopin's heart is carried back to Warsaw in secret by his adoring sister. A woman must return to her native Poland in order to poison her terminally ill high school sweetheart, and a young man slowly descends into madness when his wife and child mysteriously vanish during a vacation and just as suddenly reappear. Through these brilliantly imagined characters and stories, interwoven with haunting, playful, and revelatory meditations, Flights explores what it means to be a traveler, a wanderer, a body in motion not only through space but through time. Where are you from? Where are you coming in from? Where are you going? we call to the traveler. Enchanting, unsettling, and wholly original, Flights is a master storyteller's answer.